Environmental Potentials of Asphalt Mixtures Fabricated with Red Mud and Fly Ash - Siverio Lima, Mayara S.; Hajibabaei, M.; Thives, L.P.; Haritonovs, V.; Buttgereit, A.; Queiroz, C.; Gschösser, F. (Taylor and Francis, 2021)
Several studies evaluated the feasibility of using residues to compose asphalt mixtures. However, the demand for treatments are often neglected in determining the environmental impacts. This study aims to elucidate the decision-making process over the application of residues (e.g., red mud and fly ash) to produce asphalt mixtures. For comparison purposes, limestone and dolomite are used as reference fillers. The cradle-to-gate approach is applied within three scenarios. In the first scenario, the treatment of the residues is included in the modelling, the second excludes treatment, and the third scenario evaluates the environmental impacts of the residues deposited in landfills. To perform the analysis, indicators such as Global Warming Potential, Acidification, and Cumulative Energy Demand are applied. The results show that the treatment provided to the residues strongly influences the environmental impacts of the production of asphalt mixtures and may be crucial to define the feasibility of the residues application.